Causes and Consequences of Drug/Alcohol Addiction among Youth: Exploring the Impact of Alcohol Addiction on Youth in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
An immense scope of treatment choices going from psychological to social and furthermore motivator based projects has regularly treated substance misuse cases. Aims To assess the factors influencing alcohol addiction and their impact on personal, family, and social life among patients attending Mental illness alcohol and drug addiction psychiatric nursing home and rehabilitation centre in India. Research Methodology-The selection of the most appropriate research design method depends on the objectives of the study. Data analysis -In this Paper, the quantitative and qualitative data obtained from the selected respondents has been analyzed. Conclusion-The objectives are to assess the various factors leading to alcohol addiction, to assess the influence of addiction on personal, family, and social life, and also to create awareness among the community with regard to the causes, impact, and ill-effects of alcohol addiction.